ANALISIS PENGARUH CAR, NIM, BOPO DAN LDR TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2011 SAMPAI DENGAN TAHUN 2015 - Ramadhani Indah Saputri (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study was to describe (1) the effect of CAR, NIM, BOPO and LDR on stockreturn, (2) the effect of CAR on stock return, (3) the effect of NIM on stock return, (4) the effectof BOPO on stock return and (5) the effect of LDR on stock return. The population is allbanking companies listed on the Stock Exchange in 2011-2015 with a sample of 23 companies.Data collection using a documentation, while data analysis techniques using multipleregression analysis and the classical assumption test. The magnitude of the effect seen from thecoefficient of determination (R2) trough multiple regression analysis that is equal to 0,217. Theresults show that the coefficient determinant of leadership CAR, NIM, BOPO and LDR have apositive influence on employee performance by 21,7% and the remaining 78,3% is in influencedby other factors.